Optimization Of Welding Parameters On Mechanical Properties Of Aluminium Alloy 7075 - Yomli, Sofia Mulyani (2019)
This project is to study the effects of welding parameters for aluminium alloy 7075 towards the material characterization. The welding process used is Gas Metal Arc Welding (GMAW). The raw material used in this project is Aluminium Alloy (AA) 7075 and welded by using the KUKA robotic welding machine. The AA7075 was butt jointed with constant bevel angle which is 60°. There are three most important parameters of GMAW process that have been identified, which are current (A), voltage (V) and travel speed (S). The experiment is designed by using Design of Experiment (DOE) which is Response Surface Methodology (RSM) method. RSM method and Analysis of Variance (ANOVA) are used to optimize and validate the welding parameters. After that, the workpiece was cut into 11 samples with required dimensions in a dumbbell shape specimen by using wire EDM machine. Then the tensile test is conducted to observe the ultimate tensile strength (UTS), tensile modulus and also percentage elongation. The highest value of UTS obtained is 185.989 N/mm?. While the highest value of tensile modulus obtained is 20.44 N/mm?. For percentage elongation, the highest value obtained is 6%. Next, the Vickers hardness test is conducted to observe the hardness value which is measured to organize the revolution of mechanical property of weldment area. The highest value of hardness obtained is 89.3 HV. In addition, the microstructure of the sample is observed by using an optical microscope. It is to observe the length of the Heat Affected Zone (HAZ), grain size of weldment area and base metal. Multi-objective result shows that welding current at 143.7855 A and welding speed at 0.5329 m/min which 183.2128 MPa for UTS, 20.4992 MPa for tensile modulus, 6.3539% for percentage elongation and 88.7604 HV for hardness. Multi objective result shows that output of responses become slightly lower than single objective. This due to the multi-objective takes consideration all target.